1980
DOI: 10.1063/1.327327
|View full text |Cite
|
Sign up to set email alerts
|

Sputter-induced isotopic fractionation at solid surfaces

Abstract: Elemental and isotopic mass fractionation in both binary and multicomponent media are investigated within the framework of the familiar collision-cascade model for sputtering. Some of the most salient features of the phenomenon are explicable on this basis. It is found that the partitioning of beam-deposited energy among the various target components can account for differentiations in the secondary recoil fluxes only on the order of one part per thousand, indicating the importance of the surface potentials wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

1981
1981
1987
1987

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The 'surface flux' model was adopted because the nonstoichiometric emission of isotope species expected from the bulk recoil flux alone was found to be much smaller than indicated by experiment. Thus Russell et al [1980] found 8(n•Ca: 4øCa) for material sputtered from a plagioclase target to be on the order of • -20% o, while predictions based on nonstoichiometries in the bulk recoil flux indicated values no less than -1%o [Watson and Haft, 1980]. On the other hand, the surface flux model is in adequate agreement with the data 2, respectively, and furthermore we define AM/M, --e. To il-of Russell et al [1980] for Ca fractionation in plagioclase and lustrate the fractionation behavior for small mass differences in fluorite.…”
mentioning
confidence: 51%
See 4 more Smart Citations
“…The 'surface flux' model was adopted because the nonstoichiometric emission of isotope species expected from the bulk recoil flux alone was found to be much smaller than indicated by experiment. Thus Russell et al [1980] found 8(n•Ca: 4øCa) for material sputtered from a plagioclase target to be on the order of • -20% o, while predictions based on nonstoichiometries in the bulk recoil flux indicated values no less than -1%o [Watson and Haft, 1980]. On the other hand, the surface flux model is in adequate agreement with the data 2, respectively, and furthermore we define AM/M, --e. To il-of Russell et al [1980] for Ca fractionation in plagioclase and lustrate the fractionation behavior for small mass differences in fluorite.…”
mentioning
confidence: 51%
“…The expression given by (2) and hence the result (6) arise from a detailed solution of the transport equation describing energy sharing among recoiling atoms [ Watson, 1980;Watson and Haft, 1980]. A source of particles is created by primary collisions between the incident ion and a target atom.…”
Section: 5%0 For the Magnitude Of The Fractionation Effect (See Figurementioning
confidence: 99%
See 3 more Smart Citations